Dental implant surfaces and their interaction with the oral microbiome - Jon J. Vernon; El Mostafa Raïf; Jensen Aw; Ed Attenborough; Animesh Jha; Thuy Do (Elsevier, 2022)
Objective: This review aims to collate the current knowledge in the field of antimicrobial surfaces on dental implant materials, focusing on microbial population and functional responses, predominantly from omics-based studies. Design: Extensive searching of Scopus and Pubmed databases informed a narrative review on the antimicrobial impact of implant surfaces on the complex oral microbiome. Results: The awareness of this issue has led to considerable research resources being directed towards the augmentation of implant surfaces to counteract microbial colonization. Whilst the implant material itself has a direct influence on bacterial adhesion and viability, the surface finish and putative antimicrobial coatings are critical to countering early biofilm formation. Multiple modes of surface modification have been developed to counteract early colonization, including direct physical contact effect, such as anti-adhesion strategies and extract effects, through antimicrobial release chemistry or material leaching. These concepts deploy different techniques, including nano-texturing, surface chemistry alteration and controlled release, each with a diverse set of benefits and drawbacks. Novel surface finishes and coatings require investigation with regards to their influence on oral biofilms, whether on individual bacterial species or against mature biofilms. Conclusion: The search for optimal implant surfaces is necessary for the reduction of the peri-implantitis burden and the longevity of dental implants. To date, next generation sequencing methodologies, enabling a greater depth of understanding of the complex interactions between oral microorganisms, host response, and implant surface coatings are under used in this area of research.